Job shock : four new principles transforming our work and business - Dent, Harry S., 1950- (New York : St. Martin's Press, 1995)
American companies are experiencing a fundamental change. Massive layoffs, plant closings, cost cutting, and benefit slashing have created a climate of fear. From CEOs to middle managers to salespeople to factory workers to order-entry processors, employees at every level wonder, What will happen to my job? Do I have any security? Where have all the old rules gone? Job Shock describes the brave new world of work - a full-scale revolution that is changing the American economy from top to bottom. The early symptoms of this revolution maybe unsettling, but the future is overwhelmingly positive: a world where technologies empower the individual worker, bringing exciting opportunities and creativity to every career and destroying the rigid corporate structure that has ruled for more than a century. In this book, economic forecaster and best-selling author Harry Dent offers bold predictions about the next ten years and sound advice on how you can prepare.
Keywords: Organizational change; Career development; Manpower planning; Labor supply -- Effect of automation on; Information technology -- Management